2014
DOI: 10.1002/ps.3813
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adaptation to a new host in a generalist herbivore: implications for host plant resistance to twospotted spider mites in cotton

Abstract: This 'negative adaptation' indicates robust antibiosis traits in G. arboreum accession BM13H, which therefore have value in developing mite-resistant G. hirsutum cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This could be because the thrips had adapted to the bean plants to some extent after more than one generation. Miyazaki et al (2015) also found an initial reduction in fitness when two‐spotted spider mites changed hosts, followed by rapid adaptation to the new host.…”
Section: Discussionmentioning
confidence: 95%
“…This could be because the thrips had adapted to the bean plants to some extent after more than one generation. Miyazaki et al (2015) also found an initial reduction in fitness when two‐spotted spider mites changed hosts, followed by rapid adaptation to the new host.…”
Section: Discussionmentioning
confidence: 95%
“…The enzyme activities increased from the F 2 generation regardless of which food was fed to the thrips, which indicated that the thrips had adapted to feeding on higher quality food after the first generation. Consistently, transferring two-spotted spider mites to new hosts decreased their fitness more than they rapidly adapted to the new host, before increasing their fitness within 5 generations ( Miyazaki et al 2015 ). Additionally, after 3 or more generations of adaptation, the digestive enzyme activities in the second-instar larvae and adults of WFTs became stable on transformed hosts, and similar enzyme activities were also reported in Bemisia tabaci ( Li 2009 , Zhou et al 2010 ).…”
Section: Discussionmentioning
confidence: 98%
“…The chemical control of TSSM is relatively expensive and can select for resistance in the mite populations. Exploiting host plant resistance traits to TSSM is a current breeding target for the program and novel germplasm with resistance is now part of the commercial breeding pipeline (Miyazaki et al, 2012(Miyazaki et al, , 2015. Our breeding efforts show that the incorporated TSSM resistance has remained high across consecutive backcross generations when compared to commercial controls (Figure 4).…”
Section: Two-spotted Spider Mitementioning
confidence: 90%